Usaha Pemanfaatan Lahan Pekarangan Budidaya Tanaman Sayuran Secara Vertikultur Pada Kelompok Ibu-Ibu ‘Aisyiyah - Juita Rahmadani Manik; Muhammad Alqamari; Andini Hanif (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
The yard in Medan Denai Subdistrict is actually still quite extensive, but most of it is not used for vegetable crops so it is not possible to plant other crops such as vegetables. The main problems that occur in the target community are 1) there are not many activities of the Aisyiyah mothers group related to community empowerment, 2) the yard environment in Medan Denai District is largely untapped for vegetable crops, 3) most members of Aisyiyah do not have knowledge , insight and skills in intensifying the land area to be more productive and provide added value to the community, and 4) the potential of human and natural resources in Medan Denai Subdistrict has not been utilized optimally. To achieve the stated objectives, several methods are used, namely: 1) counseling, which is conducted by gathering organizational leaders and pilgrims to participate in counseling on women's empowerment, managing land and verticulture cultivation technology, with resource persons from the Implementation Team, 2) technology transfer by procuring verticultural installations with various models, as well as preparing other facilities that support this activity, 3) demonstration and training carried out by simulating verticulture cultivation practices using equipment and materials prepared by program implementers, 4) verticulture cultivation practices to produce products , and 5) periodic accompaniment to foster and assist partners until they successfully carry out verticultural cultivation until they achieve optimal results. The results of the Kemuhammadiyaan Coaching program show that the Coaching program provides great benefits for program participants because it can increase the insight, knowledge and skills in using the land so that it becomes more productive.